PROBLEMATIKA GURU DALAM MERENCANAKAN PEMBELAJARAN IPAS DI KELAS V SD NEGERI 2 MANURUNGE KABUPATEN BONE - Sudarto, Sudarto; Sitti Jauhar; Nurul Fitri Muin (JOEL: Journal of Educational and Language Research, 2024)
This research is a qualitative study which aims to determine the problems of teachers in designing the IPAS learning in the 5th Grade. The subjects of this research were the 2 teachers of Grade VA and VB at SD Negeri 2 Manurunge. Data collection techniques were carried out by interviews. The data analysis technique was carried out using the Miles and Huberman model which consists of : data reduction, data presentation and drawing conclusions. The results of this research showed that teachers' problems in planning IPAS learning in Grade V of SD Negeri 2 Manurunge, Bone Regency includes: difficult in preparing appropriate media according to the demands of the independent curriculum, difficult in creating teaching modules, CP, TP, and ATP related to science and science learning, it is difficult to determine the right teaching method, it is difficult to prepare science as learning due to differences in students' IQ levels, it is difficult to prepare the right science and learning materials and media, and it is difficult to carry out the IPAS practicum